2009
DOI: 10.1074/jbc.r800081200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Protein Interactions Drive Membrane Protein Topogenesis in Accordance with the Positive Inside Rule

Abstract: Transmembrane domain orientation within some membrane proteins is dependent on membrane lipid composition. Initial orientation occurs within the translocon, but final orientation is determined after membrane insertion by interactions within the protein and between lipid headgroups and protein extramembrane domains. Positively and negatively charged amino acids in extramembrane domains represent cytoplasmic retention and membrane translocation forces, respectively, which are determinants of protein orientation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 28 publications
2
57
0
1
Order By: Relevance
“…Testing the Lipid-dependent Charge Balance Hypothesis with PheP-We suggested that polytopic membrane proteins containing competing opposite charges on one side of the membrane might share a common mechanism for topogenesis (1,14,19). To further test this hypothesis, we extended our studies to PheP as another model protein with little homology to the sugar permeases.…”
Section: C4 Domain Mutation(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…Testing the Lipid-dependent Charge Balance Hypothesis with PheP-We suggested that polytopic membrane proteins containing competing opposite charges on one side of the membrane might share a common mechanism for topogenesis (1,14,19). To further test this hypothesis, we extended our studies to PheP as another model protein with little homology to the sugar permeases.…”
Section: C4 Domain Mutation(s)mentioning
confidence: 99%
“…Therefore, it was concluded that interaction between the collective charge properties of the membrane surface and the protein cytoplasmically exposed extramembrane domains directs the final orientation of TMs (i.e. the effects of changes in net charge were the same whether resulting from the lipid or the protein) (14,19). A role for lipids with no net charge appears to be a dampening of the translocation potential of negative residues that work in opposition to the positive inside rule.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane proteins are arranged such that positively charged residues localize to the intracellular membrane face (4). The structural basis of this phenomenon is the interaction of anionic lipids, which are concentrated to the intracellular membrane leaflet, with cationic protein residues (5,6). This fundamental mechanism implies that anionic lipids also compete with electrostatic interactions between transmembrane (TM) 3 helices within the intracellular lipid headgroup region.…”
mentioning
confidence: 99%